COMPARATIVE ANALYSIS OF MILLING-BAKERY AND CONFECTIONERY INDUSTRY IN SERBIA BASED ON BENFORD’S LAW - Petrović, Dragana; Novović, Milan; Šoškić, Milan (Economics of Agriculture, 2025)
This study aims to apply Benford’s Law when detecting fraud and errors in financial statements. The research includes the practical use of this law on examples of large and medium-sized enterprises in the milling, baking and confectionery industry in Serbia. Based on the conducted data analysis and the obtained results, the authors ranked the companies, after which, through a comparative analysis between these two branches, they showed which data in the Cash Flow Report have greater deviations from Benford’s analysis. The obtained data are determined by means of a statistical investigation of the probability distribution of a random variable, where it should be borne in mind that data with lower figures are expected to be more numerous than data with higher figures. The results of the analysis tabularly and graphically present an overview of the movement of cash flows of companies in the milling, baking and confectionery industry.